The rhetoric of de-policing: Evaluating open-ended survey responses from police officers with machine learning-based structural topic modeling. (September 2019) - Mourtgos, Scott M.; Adams, Ian T.
Highlights: Machine learning-based textual analysis is a viable tool for police survey research Analyzing large numbers of police free-text responses provides more nuanced understanding of police perceptions of the public Officers' attention to professionalism guards against de-policing, while attention to perceived unfair criticism increases it The public's integrity has a stronger effect on propensity to de-police than the public's knowledge about police work